2007
DOI: 10.4049/jimmunol.178.1.605
|View full text |Cite
|
Sign up to set email alerts
|

Th1 and Type 1 Cytotoxic T Cells Dominate Responses in T-bet Overexpression Transgenic Mice That Develop Contact Dermatitis

Abstract: Contact dermatitis in humans and contact hypersensitivity (CHS) in animal models are delayed-type hypersensitivity reactions mediated by hapten-specific T cells. Recently, it has become clear that both CD4+ Th1 and CD8+ type 1 cytotoxic T (Tc1) cells can act as effectors in CHS reactions. T-bet has been demonstrated to play an important role in Th1 and Tc1 cell differentiation, but little is known about its contribution to CHS. In the present study, we used C57BL/6 mice transgenic (Tg) for T-bet to address thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 37 publications
(43 reference statements)
3
45
0
Order By: Relevance
“…ϩ Th cells (38). Activated NK cells produce large amounts of IFN-␥, potentiate Th1 priming, and also participate in the CHS reaction (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…ϩ Th cells (38). Activated NK cells produce large amounts of IFN-␥, potentiate Th1 priming, and also participate in the CHS reaction (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…T-bet expression in these mice is under the control of the human CD2 promoter, which allows it to be expressed exclusively in CD2-expressing cells. 10,11 In the present study, we further explored these mice, focusing in particular on the hematopoietic system, especially hematopoiesis of the mononuclear phagocyte lineage. Unexpectedly, we found that aged transgenic mice homozygous for the hCD2-T-bet tg allele spontaneously developed a pulmonary disease resembling human pulmonary alveolar proteinosis (PAP), a rare lung disorder characterized by the accumulation of surfactant protein within alveolar spaces due to functional defects in alveolar macrophages, and accompanied by local and bone marrow (BM) mononuclear phagocyte dysregulation.…”
Section: Naïve Cd4mentioning
confidence: 99%
“…11 We began by monitoring the viability of the littermates from hCD2-T-bet tg/wt (T-bet tg/wt ) mice. Of note, starting at ;20-weeks of age, more than 80% of the homozygous transgenic (T-bet tg/tg ) mice became moribund and died under For personal use only.…”
Section: T-betmentioning
confidence: 99%
“…T-bet tg/tg mice were generated as previously described (14) and backcrossed to BALB/c mice for eight generations. T-bet 2/2 BALB/c mice were obtained from the The Jackson Laboratory (Bar Harbor, ME).…”
Section: Mice and Infectionmentioning
confidence: 99%